Elucidating the Structural Features of ABCA1 in its Heterogeneous Membrane Environment - Sunidhi, S.; Sacher, Sukriti; Atul,; Garg, Parth; Ray, Arjun (Frontiers in Molecular Biosciences, 2022)
ATP Binding Cassette Transporter A1 (ABCA1) plays an integral part in Reverse Cholesterol Transport (RCT) and is critical for maintaining lipid homeostasis. One theory of lipid efflux by the transporter (alternating access) proposes that ABCA1 harbours two different conformations that provide alternating access for lipid binding and release. This is followed by sequestration via a direct interaction between ABCA1 and its partner, ApoA1. The other theory (lateral access) proposes that ABCA1 obtains lipids laterally from the membrane to form a temporary extracellular “reservoir”. This reservoir contains an isolated lipid monolayer due to the net accumulation of lipids in the exofacial leaflet. Recently, a full-length Cryo-EM structure of this 2,261-residue transmembrane protein showed its discreetly folded domains and have detected the presence of a tunnel enclosed within the extra-cellular domains (ECDs) but not in the TMDs giving it an outward-facing conformation. This structure was hypothesized to substantiate the lateral access theory. Utilizing long time-scale multiple replica atomistic molecular dynamics simulations (MDS), we simulated the structure in a large heterogeneous lipid environment and found that the protein undergoes several large conformational changes in its extremities. We observed that the cavity enclosed within ATP unbound form of ABCA1 is narrow at the distal ends of TMD as well as ECD region substantiating the “lateral access” theory. We have also characterized ABCA1 and the lipid dynamics along with the protein-lipid interactions in the heterogeneous environment, providing novel insights into understanding ABCA1 conformation at an atomistic level.